2021
DOI: 10.3390/f12111451
|View full text |Cite
|
Sign up to set email alerts
|

Lean Pattern in an Altitude Range Shift of a Tree Species: Abies pinsapo Boiss.

Abstract: Organisms modify their geographical distributions in response to changes in environmental conditions, or modify their affinity to such conditions, to avoid extinction. This study explored the altitudinal shift of Abies pinsapo Boiss. in the Baetic System. We analysed the potential distribution of the realised and reproductive niches of A. pinsapo populations in the Ronda Mountains (Southern Spain) by using species distribution models (SDMs) for two life stages within the current populations. Then, we calculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 45 publications
2
4
0
Order By: Relevance
“…In the case of A. alba, despite encompassing the largest current distribution, the forecasted scenarios do not ensure an extensive potential distribution, taking into consideration climate change. On the other hand, the Abies genus seemed to be resilient to climate change, showing that a latitudinal and an altitudinal upward migration could be feasible as a response to the changing bioclimatic conditions expected over the next few decades (González-Hernández et al 2021). According to our results, the general potential distribution of genus Abies could increase in the circum-Mediterranean.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…In the case of A. alba, despite encompassing the largest current distribution, the forecasted scenarios do not ensure an extensive potential distribution, taking into consideration climate change. On the other hand, the Abies genus seemed to be resilient to climate change, showing that a latitudinal and an altitudinal upward migration could be feasible as a response to the changing bioclimatic conditions expected over the next few decades (González-Hernández et al 2021). According to our results, the general potential distribution of genus Abies could increase in the circum-Mediterranean.…”
Section: Discussionsupporting
confidence: 56%
“…Species which have suffered a contraction of their original geographic distribution, through the years due to climate change are known as climate relicts. In order to avoid extinction, these organisms modify their geographical distribution or their affinity to the new conditions brought about by environmental changes (González-Hernández et al 2021). The former trait is related to the migration speed, i.e., the relocation of the plant in response to the effects of climate change.…”
Section: Introductionmentioning
confidence: 99%
“…The main species distribution models indicate an overall decline in the forest mass in the southern part of the Iberian Peninsula. Special interest has been shown in the models applying to the A. pinsapo (Alba-Sánchez and López-Sáez, 2013; Alba-Sánchez et al, 2010; Gonzalez-Hernandez et al, 2021; Gutiérrez-Hernández, 2018; Navarro-Cerrillo et al, 2006, 2013; Sánchez-Salguero, 2007), based on patterns of suitability and multivariable regressions to establish different degrees of potentiality regarding the previous presence of this species in the mountains in the south and south-east of Spain (Serranía de Ronda, Sierras de Almijara-Tejeda, Sierra Nevada, Sierras de Cazorla-Segura and Sierra de Aitana).…”
Section: Resultsmentioning
confidence: 99%
“…For their part, the models developed by González-Hernández et al (2021) highlight the mismatch between the current niche and the reproductive niche of A. pinsapo in response to a changing climate. These authors observed a change in the altitude range, where the young trees are migrating upwards (or northwards) toward cooler and wetter climates leaving behind the older generations of trees to try to survive at lower altitudes.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the climate change, Mediterranean high‐mountain endemic species are particularly vulnerable. González‐Hernández et al (2021) discovered a disparate demographic structure of Spanish fir ( Abies pinsapo Boiss. ), that is, in populations at different elevations in Cádiz and Málaga provinces, young saplings were found at higher elevations than mature trees i.e.…”
Section: Key To the Taxa Studiedmentioning
confidence: 99%